Congenital Myotonic Dystrophy type 1: prenatal manifestations regarding a case - Licourt Otero, Deysi; Toledo Licourt, Melissa; Candelaria Gómez, Belkys; Díaz Hernández, Ilena Aurora (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introductions: myotonic dystrophy type 1 is a genetic disorder with great clinical variability in which there is a positive association between the number or size of the cytosine, thymine, guanine triplet repeats and the severity of the manifestations. The disorder exhibits an intergenerational anticipation phenomenon that explains the earlier age of onset of signs and the greater expression of clinical signs. Objetive: to describe the prenatal manifestations of myotonic dystrophy type 1. Clinical case: 22-year-old female patient with a diagnosis of DM1 since she was 6 years old and with a family history of the disorder through the mother’s line who came to the clinic with a 22-week pregnancy. Multiple signs were reported when performing prenatal fetal ultrasonography due to: presentation maintained in the pelvic region, slight ventriculomegaly, lower limbs extended and with ventral flexion on the trunk as well as both equinus feet. The birth occurred with a gestation period of 33.6 weeks, the Apgar test was 3-3-3, birth weight 2450 gr. Conclusions: the severity of the congenital form of myotonic dystrophy type 1 requires close monitoring by a multidisciplinary team that extends from the preconception stage, to detect the possible complications described that worsen the quality of life of patients and their families, and may even to the death of both the mother and the newborn, especially during the first year of life.